Changes in organic carbon in soil of natural grassland converted to Pinus taeda plantations at three ages - Cassol,Paulo Cezar (2019)
Abstract Pine plantations on former natural grassland (NG) areas can change the forms and stocks of organic carbon (OC) in the soil. To quantify these changes, the contents and stocks of the total OC (TOC), consisting of particulate OC (POC) and the mineral-associated OC (MAC) fractions, were determined in five layers, at depths between 0.0 and 0.40 m, in soil under NG and pine plantations aged five (P5), 16 (P16) and 21 (P21) years. The study was carried out in areas of Cambissolo Húmico, dystrophic, on the southern plateau of Santa Catarina state. The TOC content in the different layers and under different land uses ranged from 15.0 to 44.5 g kg-1 and the TOC stock, in all layers together, from 86 to 144 Mg ha-1. The POC content varied from 2.1 to 23.2 g kg-1 and the POC stock from 7.4 to 21.8 Mg ha-1, while the MAC content varied between 12.2 and 23.7 g kg-1 and MAC stock between 79 and 122 Mg ha-1. In general, the TOC stocks and contents and MAC and POC fractions in the soil increase with the age of the pine plantations up to 21 years. The TOC and POC contents and POC stock usually decrease with depth under NG, P5 and P21, whereas the MAC content and MAC and TOC stocks generally remain unchanged in layers to a depth of 0.40 m.